2012
DOI: 10.2337/dc12-er11b
|View full text |Cite
|
Sign up to set email alerts
|

Improved metabolic control in children and adolescents with type 1 diabetes: a trend analysis using prospective multicenter data from Germany and Austria. Diabetes Care 2012;35:80–86

Abstract: on behalf of the DPV Initiative and the German BMBF Competence Network Diabetes Mellitus. Improved metabolic control in children and adolescents with type 1 diabetes: a trend analysis using prospective multicenter data from Germany and Austria. Diabetes Care 2012;35:80-86In the print version of the article listed above, there is an error in Fig. 1. The vertical whiskers in Fig. 1F representing 95% CIs were not correctly drawn. The corrected Fig. 1F appears below. The online version reflects these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 0 publications
6
61
0
2
Order By: Relevance
“…In our group of patients, the age at which they were diagnosed with diabetes did not affect the disease's metabolic control or without a statistically significant difference, was found (P. = 0.260) which is in agreement with this study (15)(16)(17) . The duration of type 1 diabetes <= 5 years, in uncontrolled hyperglycemia diabetes patients, was the highest (64.2%), when the mean of age for all subjects is 4.26 ± 3.407 years old, as well in well-controlled T1DM patients <= 5 years was the highest (86.1%) when the mean of age for all subjects is 3.22 ± 3.072 years old, with a statistically significant difference, was found (P. = 0.031) which is in agreement with this study (13) .…”
Section: Table (1) the Basic Socio-demographic Characteristics Of The Study Samplesupporting
confidence: 92%
See 1 more Smart Citation
“…In our group of patients, the age at which they were diagnosed with diabetes did not affect the disease's metabolic control or without a statistically significant difference, was found (P. = 0.260) which is in agreement with this study (15)(16)(17) . The duration of type 1 diabetes <= 5 years, in uncontrolled hyperglycemia diabetes patients, was the highest (64.2%), when the mean of age for all subjects is 4.26 ± 3.407 years old, as well in well-controlled T1DM patients <= 5 years was the highest (86.1%) when the mean of age for all subjects is 3.22 ± 3.072 years old, with a statistically significant difference, was found (P. = 0.031) which is in agreement with this study (13) .…”
Section: Table (1) the Basic Socio-demographic Characteristics Of The Study Samplesupporting
confidence: 92%
“…This result shows that well-controlled diabetes in females was higher than in males, which is in agreement with other studies like these by (1,(8)(9)(10)(11) , with no statistically significant difference, was found (P = 0.557). For body mass index, the median with uncontrolled hyperglycemia diabetes T1DM patients (18.48 kg/m2) was significantly less than that in well-controlled diabetes in T1DM patients (18.89 kg/m2), (P. = 0.009), may be associated with uncontrolled hyperglycemia diabetes and corresponds with the studies by (12,13) . The present study found that among the sampled population with uncontrolled hyperglycemia diabetes T1DM patients, 101 (58.4%)…”
Section: Introductionsupporting
confidence: 80%
“…Diabetes care in general differs not only on an individual basis but also between diabetes centers on a national and even more on an international basis 6–8 . Benchmarking and comparison of diabetes care through diabetes registries improved patient outcomes significantly over the years 9,10 . Furthermore, it raised awareness for differences in diabetes care between countries 6,11–13 .…”
Section: Introductionmentioning
confidence: 99%
“…HbA1c was measured locally in each center; to adjust for differences between laboratories, the multiple of the mean method was used to standardize local HbA1c mathematically to the DCCT reference of 20-42 mmol/mol (4-6%). The BMI was calculated from registered height and weight as weight/squared height (kg/m [2]) and converted to BMI-SDS (standard deviation score) using WHO growth curves [16,17]. Blood pressure was assessed according to Fourth Report [18] ("Fourth Report on the Diagnosis, Evaluation, and Treatment of High Blood Pressure in Children and Adolescents").…”
Section: Data Source and Participantsmentioning
confidence: 99%